Steering the Nexus: iZindaba Zokudla and Governing for Sustainability - Malan, Naudé (Frontiers in Sustainable Food Systems, 2021)
“iZindaba Zokudla” means we talk about the food that we eat. iZindaba Zokudla is a public innovation lab that uses stakeholder-engagement methods to create “opportunities for urban agriculture in a sustainable food system.” iZindaba Zokudla is presented as an extra-institutional means to govern the water, land, energy, and waste nexus. This reflective essay critically describes iZindaba Zokudla and applies this to the design of institutional steering mechanisms to govern the food, water, land, and energy nexus towards sustainability. Governance is an intersubjective and interactive process between the subjects of governance and governance itself. Sustainability, as an interactive process, implies the creation of autocatalytic and symbiotic communities in society that integrates diverse actors and stakeholders, inclusive of scientific and lay actors, and ecosystems. iZindaba Zokudla is a means to govern and create such communities, and this article describes and reflects on how iZindaba Zokudla has created and managed such symbiotic communities or autocatalytic networks in the food system. The article generalises how the activities conducted in iZindaba Zokudla can be used to govern the water, land, energy, and waste nexus for sustainability. The article shows how iZindaba Zokudla has realised a progressive governance through the facilitation of its Farmers' Lab and website; how it has created opportunities for participation; and how it enables critical reflection in society.